ANALYSIS OF THE INFLUENCE OF CURRENT RATIO, DEBT TO EQUITY, FIRM SIZE, MANAGERIAL OWNERSHIP, NET PROFIT MARGIN ONPROFITABILITY IN MANUFACTURING COMPANIES INCONSUMPTION GOODS SECTOR - Yois Nelsari Malau; Natasya Nainggolan; Ribka Sujana; Nurul Aulia; Andreas Randy Wangary (Jurnal Ipteks Terapan, 2023)
This study aims to prove and analyze the effect of Current Ratio, Debt to Equity Ratio, Firm Size, Managerial Ownership, Net Profit Margin on Profitability in manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange in 2018-2021.The population in this study is 51 companies listed on the Indonesia Stock Exchange in 2018-2021. Of the 51 listed companies, 18 sample companies were selected using purposive sampling. The data used in this study is secondary data, by collecting the information needed from idx financial in the form of financial statements for 2018-2021. The results of the study simultaneously with the F test showed that the variables current ratio, debt to equity ratio, firm size, managerial ownership, net profit margin affect profitability. The results of the discussion with the T test showed that the variables current ratio, debt to equity, firm size, managerial ownership and net profit margin. Keywords: Current Ratio, Debt to Equity, Firm Size, Managerial Ownership, Net Profit Margin, Profitability